2002
DOI: 10.1080/10550490290088018
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Cigarette Smoking, Alcohol Use and Other Substance Use Among Chinese University Students in Hong Kong

Abstract: The pattern of tobacco, alcohol, and other substance use was assessed among 1,197 Chinese undergraduates in Hong Kong. Students reported their current and past use of tobacco (13%), alcohol (61%), marijuana (2%), and other illicit drugs (0.4%). Perceptions of risk from the use of different substances were low among those who use substances and among senior students. The rate of substance use was higher among males, residents of university hall, senior students, and among those who possessed a positive attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 32 publications
3
17
1
2
Order By: Relevance
“…Risk markers for potential high risk sexual behaviours such as alcohol and tobacco use, but not illicit drug use, are more prevalent among the Chinese than the non-Chinese population (Cappon et al, 1996;Abdullah et al, 2002a). In this study, increasing alcohol use is associated with no increase in risk taking among non-Chinese, but among Chinese is a marker for significantly higher risk.…”
Section: Non-chinese Non-chinese Individuals In Hongmentioning
confidence: 70%
“…Risk markers for potential high risk sexual behaviours such as alcohol and tobacco use, but not illicit drug use, are more prevalent among the Chinese than the non-Chinese population (Cappon et al, 1996;Abdullah et al, 2002a). In this study, increasing alcohol use is associated with no increase in risk taking among non-Chinese, but among Chinese is a marker for significantly higher risk.…”
Section: Non-chinese Non-chinese Individuals In Hongmentioning
confidence: 70%
“…We found that there were no significant relationships between social background and the substance use of university students, findings concurrent with several other studies. 3,4,9,10,14,15,16 There may be some underestimation of the prevalence of substance use as a result of the absentees being omitted from the student population and possibly some incorrect answers about personal substance use because this is illegal in Turkey. As any other targeted study, there are limitations about the representativeness of the sample of the present study, but while the prevalence indicators of substance use may vary in other universities in Turkey, the factors associated to substance use are unlikely to differ, and this is the first large-scale multicenter university survey which investigated correlates of substance use problems.…”
Section: Discussionmentioning
confidence: 99%
“…University students constitute a high risk group regarding the adoption of risky behavior, such as smoking and illicit substance use [5, 6]. University students are prone to risk-taking behavior, which has been associated with the underdevelopment of the orbital-frontal cortex [7].…”
Section: Introductionmentioning
confidence: 99%